Endosymbiotic bacteria in insects: guardians of the immune system? - Eleftherianos, Ioannis; Atri, Jaishri; Accetta, Julia; Castillo, Julio (Frontiers in Physiology, 2013)
Insects have evolved obligate, mutualistic interactions with bacteria without further transmission to other eukaryotic organisms. Such long-term obligate partnerships between insects and bacteria have a profound effect on various physiological functions of the host. Here we provide an overview of the effects of endosymbiotic bacteria on the insect immune system as well as on the immune response of insects to pathogenic infections. Potential mechanisms through which endosymbionts can affect the ability of their host to resist an infection are discussed in the light of recent findings. We finally point out unresolved questions for future research and speculate how the current knowledge can be employed to design and implement measures for the effective control of agricultural insect pests and vectors of diseases.